Penerapan Model Pembelajaran Berbasis Masalah Menggunakan Geogebra Untuk Mengetahui Kemampuan Komunikasi Matematis Peserta Didik - Syadiyah, Halimah As; Huda, Syaiful (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
Communication skill is an essential part in mathematics and mathematics education. Mathematics communication skill is students ability to convey ideas in solving mathematics problems both orally or written. The aim of this study is to determine students mathematics communication after the implementation of problem based learning model using Geogebra. The type of the research is descriptive quantitative. The subjects of this study are 32 students of class VII G at SMP Negeri 2 Cerme. This study uses test and interview methods to collect the data. Test method was used to determine skill of written mathematics communication and interview method was used to determine skill of orally mathematics communication. The results of this study reveals that students of class VII G at SMP Negeri 2 Cerme have mathematics communication skill high, medium, and low. The details are 12 of 32 students have high category mathematics communication skill, 14 of 32 students are in medium category, and 6 of 32 students are in low category.